Inovasi Pelayanan Pajak Hotel Dan Hiburan Berbasis Online Di Badan Pendapatan Daerah Kota Makassar - Agus, Agus; Ansari, Isa; Nasrulhaq, Nasrulhaq (Universitas Muhammadiyah Makassar, 2021)
ABSTRACTThe purpose of this study was to find out how the Online-Based Hotel and Entertainment Tax Service Innovation at the Makassar City Regional Revenue Agency. This study used qualitative description research methods and data collection techniques used interviews, observation and documentation. The results of the study showed that online-based hotel and entertainment tax service innovations at the Makassar City Regional Revenue Agency were part of eleven types of taxes that incorporated in the